EVALUATION OF INDOOR AIR QUALITY STATUS IN SELECTED COMMERCIAL BUILDINGS IN SAUDI ARABIA: ROLE OF THE HVAC SYSTEMS - Khan, Raza A. (2020)
Air quality in buildings is increasingly becoming an area of great concern because of its profound impact on occupants comfort, health and productivity. In most buildings, poor Indoor Air Quality (IAQ) can be attributed to the presence of indoor-generated pollutants and the reduced ventilation effectiveness. Recent technological advances and developments in building materials and activities have introduced numerous new pollutants to the indoor space. Additionally, trends to conserve energy and make buildings thermally more comfortable have resulted in airtight buildings, hence allowing little air leakage through their envelopes. This has resulted in the reduction or the elimination of the natural dilution process by outdoor air and increased reliance on the Heating Ventilation and Air Conditioning (HVAC) systems to dilute indoor-generated contaminants. The objective of this paper is to assess the air quality in selected commercial and office buildings in the Eastern Province of Saudi Arabia and to identify measures and considerations during building design and operation for enhancing the effectiveness of HVAC systems for better indoor air quality. Questionnaire surveys and interviews were conducted with the building occupants to assess their level of comfort. Furthermore, walk-through inspections and environmental parameters measurements were carried out in those buildings. Based upon the outcome of the analysis of the study, general guidelines have been formulated for HVAC systems design, operation & maintenance for improved IAQ in hot and humid climates of Saudi Arabia. A checklist was also developed for the evaluation of HVAC systems design, operation & maintenance to ensure proper IAQ requirements.